Pretty crazy [videorecording (DVD)] - Jones, Maurice Mo'; Taylor, Chris; Clay, Corin; Dunlap, Jasmin (Vision Films, 2022)
A successful, handsome, eligible bachelor is ready to find the one to settle down and build a future with however, the current dating climate is overwhelming. In the wake of his last relationship, he meets and falls for the perfect girl, but will his past come back to ruin his chances of them building their lives together? Dating as a millennial can be. Pretty Crazy!